Deepening democracy comparative perspectives on decentralisation, co-operativism and self-managed development - Tharamangalam, Joseph; Chathukulam, Jos
"This book examines the renewed interest and commitment that countries across the world have shown in recent decades towards adopting models of decentralizing, or "downsizing" the state, and moving towards more participatory models of government. It examines systems of decentralized development such as self-managing cooperatives from a global and comparative perspective with a focus on developing countries. Drawing on examples from Kerala and a few other states in India, as well as Cuba, Bangladesh and South Africa among other countries, the book offers critical perspectives on the positive impacts of these experiments and the promises these offer for the future. It discusses the challenges of implementing these models, how well these work in coordination with the civil society and the state, issues of transparency and democratic oversight as well as corruption and capture of power due to entrenched structures of inequality. The volume analyses welfare and development models and self-management interventions in countering the effects of the Covid-19 pandemic. It also looks at the merits and demerits of decentralization in countering the global socioeconomic and environmental crisis and the rise of authoritarian populism in many countries. The book will be of interest to students and researchers of development studies, political science, business, community development, social justice as well as of cooperative management programs. It will also appeal to students of political economy as well as development professionals, think tanks and policy makers"--Provided by publisher.